2016
DOI: 10.1080/19336918.2016.1221567
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-related receptor α participates transforming growth factor-β (TGF-β) induced epithelial-mesenchymal transition of osteosarcoma cells

Abstract: Osteosarcoma patients often exhibit pulmonary metastasis, which results in high patient mortality. Understanding the mechanisms of advanced metastasis in osteosarcoma cell is important for the targeted treatment and drug development. Our present study revealed that transforming growth factor-b (TGF-b) treatment can significantly promote the in vitro migration and invasion of human osteosarcoma MG-63 and HOS cells. The loss of epithelial characteristics E-cadherin (E-Cad) and up regulation of mesenchymal marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Thus, we focused on transcription factors binding to the MALAT1 promoter. We selected TGF-β because Chen et al [ 24 ] found that TGF-β functioned as a potent stimulator of osteosarcoma cell epithelial-mesenchymal transition. As expected, TGF-β mRNA expression was significantly increased in osteosarcoma tissues compared with the paired noncancerous tissues (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we focused on transcription factors binding to the MALAT1 promoter. We selected TGF-β because Chen et al [ 24 ] found that TGF-β functioned as a potent stimulator of osteosarcoma cell epithelial-mesenchymal transition. As expected, TGF-β mRNA expression was significantly increased in osteosarcoma tissues compared with the paired noncancerous tissues (Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in malignant bone tumors, osteosarcomas, elevated levels of ZEB1 are detected compared to normal bone and ZEB1 expression is higher in metastatic osteosarcoma in comparison with the group without metastases (Shen et al ., ). A recent study shows that TGF‐β treatment can trigger MT of osteosarcoma cells in vitro involving estrogen‐related receptor α‐dependent activation of SNAI1 (Chen et al ., ). Thus, MT may be involved in the onset and progression of sarcomas but more studies are required for further substantiation.…”
Section: Emt‐ and Met‐related Processes In Sarcomasmentioning
confidence: 97%
“…During EMT, epithelial cells reorganize their cytoskeleton to alter cell polarity and morphology, and lose their junctions, which increases the invasive capacity of the cells. The hallmarks of EMT include decreased expression of E-cadherin and overexpression of Vimentin [19,20]. In recent years, it was observed that EMT is closely related to carcinoma progression, and acts as a major driver of cellular morphogenesis and tumor progression [21].…”
Section: Introductionmentioning
confidence: 99%